Methods of fight against temperature diseases in natural damages - N.M. Omonova; Kambarova Mukhtazar (Universitas Muhammadiyah Sidoarjo, 2019)
This article analyzes soil samples of naturally occurring areas, and examines the effects of modern fungicides on fungi isolated from the infected plant when planting tomatoes on the affected area.